ANALISIS PENGAMBILAN KEPUTUSAN DALAM KENDALA DI UMKM SUMBER BAROKAH - Pebrina Kusuma Dewi; Syahra Syarafina; Rita Septia; Ujang Suherman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting the local economy. However, in practice, many MSMEs still face various challenges, particularly in business decision-making. This study aims to determine the decision-making process employed by the owners of the Sumber Barokah wet cake MSME in managing labor, capital, raw materials, and marketing. This study employed a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The results indicate that decision-making at the Sumber Barokah MSME is simple and largely based on experience and real-world conditions. Decisions are adaptive to limitations in business premises, workforce, and capital, despite the increasing number of customers. This study demonstrates that while the decisions taken are quite effective in maintaining business continuity, better planning and information utilization are still needed for MSMEs to develop sustainably.